Impact of retirement on depression, a systematic review. (30th September 2020) - Gianfredi, V; Patti, A; Amerio, A; Fracella, B; Gaetti, G; Vigezzi, G P; Odone, A
Abstract: Aim: Due to the improving of life conditions, life expectancy is steadily increasing, especially in developed countries. In this perspective, Governments have to face important challenges as guaranteeing the welfare state, providing pensions and long-term healthcare for an increasing number of people. To maintain the sustainability of the pension system, many developed countries are rising the proportion of elderly persons in paid employment by both extending working life through a higher official retirement age and preventing premature exit from paid employment. However, postponing the exit from work exposes workers to potential stressors for a longer period. Stress is one of the risk factors for depression, that represent one of the leading causes of burden of disease. Our aim is to retrieve evidence in order to understand the association between retirement and risk of depression. Methods: This is a systematic literature review, conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. In January 2020, the following databases PubMed/Medline, Embase, Psycoinfo, and Cochrane were used to perform the search, using a combination of three components of keywords: depression, aging and retirement. Results: A total of 2, 203 studies were retrieved of which 782 were excluded because duplicates. Screening of 1, 421 retrieved studies is in progress and data will be showed in tables and summarized in narrative form. Results are preliminary. Conclusions: The present research intends to bridge the lack of knowledge on the association between retirement and depression, to tackle these methodological limitations of the evidence, and to contribute to the advancement of scientific knowledge on the link between work life extension and mental health. Poor mental health is a major source of disability. Improving mental health of workers remains a critical goal if future populations need to reach older age in good health and continue to work. Key messages: Work life has been extended but low information are available regarding its impact on depression. Depression is a leading cause of burden of disease and studies aimed to reduce its incidence are extremely needed.